An innovative flow cytometry method to screen human scFv-phages selected by in vivo phage-display in an animal model of atherosclerosis. Issue 1 (December 2018) - Hemadou, Audrey; Laroche-Traineau, Jeanny; Antoine, Ségolène; Mondon, Philippe; Fontayne, Alexandre; Priol, Yannick; Claverol, Stéphane; Sanchez, Stéphane; Cerutti, Martine; Ottones, Florence; Clofent-Sanchez, Gisèle; Jacobin-Valat, Marie-Josée
Abstract Atherosclerosis is a chronic, progressive inflammatory disease that may develop into vulnerable lesions leading to thrombosis. This pathology is characterized by the deposition of lipids within the arterial wall and infiltration of immune cells leading to amplification of inflammation. Nowadays there is a rising interest to assess directly the molecular and cellular components that underlie the clinical condition of stroke and myocardial infarction. Single chain fragment variable (scFv)-phages issuing from a human combinatorial library were selected on the lesions induced in a rabbit model of atherosclerosis after three rounds ofin vivo phage display. We further implemented a high-throughput flow cytometry method on rabbit protein extracts to individually test one thousand of scFv-phages. Two hundred and nine clones were retrieved on the basis of their specificity for atherosclerotic proteins. Immunohistochemistry assays confirmed the robustness of the designed cytometry protocol. Sequencing of candidates demonstrated their high diversity in VH and VL germline usage. The large number of candidates and their diversity open the way in the discovery of new biomarkers. Here, we successfully showed the capacity of combiningin vivo phage display and high-throughput cytometry strategies to give new insights inin vivo targetable up-regulated biomarkers in atherosclerosis.